Comparison of accelerated strength testing methods as exemplified by 09G2S steel - K. V. Kuskov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
One of the urgent tasks when establishing the endurance limits of steel is limiting the time of the experiment. The main purpose of this work is to compare several accelerated methods for determining the fatigue strength: the Locati method, the method of measuring electrical resistance and the calculation method taking into account the microstructures of steel. The study was carried out on 09G2S steel in the as-delivered condition which has a ferrite-pearlite structure. As a result of the comparison, it was found that the Locati method and the method for determining the fatigue strength of low-carbon and low-alloy steels give almost identical results. The method of measuring electrical resistance gives the range of stresses in which the desired fatigue strength is located. It is shown that the first sharp jump in the change in electrical resistivity of the sample may indicate the beginning of the stage of cyclic microflow or the beginning of irreversible softening of the steel. In addition, the method of measuring electrical resistance can be useful in combination with the Locati method, when there is no data on the slope of the left branch of the fatigue curve; then using this method it is possible to determine the interval in which 3 samples need to be tested to construct this branch.